(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Corndog Station was conceptualized on February 13, 2023. We have a great atmosphere and a variety of corndogs with interesting fillings. The goal of the company’s marketing strategy is to diversify the flavor profiles of the corndogs it serves to its target market. New fillings are available at Corndog Station to satisfy our customers. Likewise, those who are eager to try something new. The business operates at Phase 2 Package 2 Block 35 Lot 13, Bagong Silang Caloocan. Perfectly established around the target market area where, which is adjacent to schools, condominiums, apartments, subdivisions, and Highways. Corndog Station will be focused on organizational structure, employee responsibilities, and company policies. It also discusses corporate social responsibility and business monitoring. Corndog Station will be unique in terms of the size of the corn dog. Our corn dogs will be bigger than normal corn dogs at the same time at an affordable price, and our sauce tastes extra spicy, cheesy, and sweet. Recognizing the target market is one of the most important steps in building a successful business. Therefore, Corndog Station has to identify and select a target market so it can direct its marketing effort to that group of customers and better satisfy their needs and wants. Corndog Station will create a good system that can be implemented inside our organization, and we will operate strategically as much as possible. We will use any kind of marketing plan, like posting on any social media platform, to promote our product and services. We also focus on Inventory control to ensure that we have enough units to fulfill orders and have safety stock. We will make sure that every part of this management has a knowledge of our production and is willing to commit to our goals.